2018
DOI: 10.12944/crnfsj.6.2.09
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Knowledge, Attitudes and Practices in Food Safety Among Food Handlers Engaged in Food Courts

Abstract: The aim of this paperis to evaluate the aspects of knowledge, attitude, and practices about food hygiene and safety issues among food handlers who are working in food courts. A cross-sectional study was conducted at four randomly food courts in Petaling Jaya, Malaysia during June and July 2017. It involves 108 respondents that match the inclusion criteria among food handlers. The guided self-administered questionnaire; were divided into three sections which are knowledge, practices, and attitudes. After the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 16 publications
(9 reference statements)
5
14
1
Order By: Relevance
“…This might be due to those food handlers who had a good level knowledge might have a higher chance of good food handling practice. This finding was supported studies conducted in Gondar town, and Malaysia [5, 15]. Marital status was another significantly associated factor with food safety practices.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This might be due to those food handlers who had a good level knowledge might have a higher chance of good food handling practice. This finding was supported studies conducted in Gondar town, and Malaysia [5, 15]. Marital status was another significantly associated factor with food safety practices.…”
Section: Discussionsupporting
confidence: 86%
“…Close to 75% of food-borne illness outbreaks are attributed to lack of safe food handling practices by food handlers in food service establishments [5]. Food handlers play a key role in ensuring strict adherence to food safety principles throughout the whole process [15].…”
Section: Introductionmentioning
confidence: 99%
“…Equipping food operators with proper guidelines and information on potential harm regarding RCO usage may encourage a more concerned attitude towards the practice of using RCO. According to Asmawi et al (2018), food operators have demonstrated poor knowledge on food safety management and handling of food. Studies conducted by Asmawi et al (2018), Azman et al (2012) and Sivananthan et al (2013) show Malaysian food operators still lack in knowledge of RCO usage.…”
Section: Food Operators' Knowledge Attitude and Practice Towards Reheated Cooking Oilmentioning
confidence: 99%
“…According to Asmawi et al (2018), food operators have demonstrated poor knowledge on food safety management and handling of food. Studies conducted by Asmawi et al (2018), Azman et al (2012) and Sivananthan et al (2013) show Malaysian food operators still lack in knowledge of RCO usage. A study conducted by Azman (2012) suggests food operators have some basic knowledge on potential risk of RCO as 67% of the study's respondents did not agree to the practice of using RCO.…”
Section: Food Operators' Knowledge Attitude and Practice Towards Reheated Cooking Oilmentioning
confidence: 99%
See 1 more Smart Citation